Виявлення змін на хромосомному рівні в еукаріотичних організмів за дії синтетичних ароматизаторів продуктів харчування та коригування їх за допомогою вітамінних хіміопревентерів - Боднар, І.В.; Зубко, О.С.; Щербакова, О.В.; Горбулінська, С.М.; Боднар, Л.С. (Фактори експериментальної еволюції організмів, 2016)
Aim. To identify changes of chromosomal level in eukaryotic organisms with the influence of synthetic flavors and possible correction of these changes with the influence of vitamin chemical preventors. Methods. Ana-telophase analysis on root meristem cells of onion Allium cepa L. and metaphase analysis on bone marrow cells of white mice Mus musculus L. in chronic and acute experiment. Results. We have shown the induction of chromosome aberrations in metaphase bone marrow cells of white mice Mus musculus L. and root meristem cells of onion Allium cepa L. by newsynthesized food flavorings «Grapes 82085p», «Petit Beurre 02974», «Chocolate 82100p», «Rafaelo 82129p», «Aromat 22062». The highest mutagen effect was identified for «Rafaelo 82129p» flavor. For correction of mutagenic background we have used the vitamin chemical preventors (vit. A and C) which reduced or removed to spontaneous levels of induction of chromosomal aberration in Mus musculus L. Conclutions. We have identified the induction of chromosomal aberrations in prolipherative cells of plant object Allium cepa and animal cells of Mus musculus with the influence of different doses of flavors. Simultaneous feeding of mice by flavorings and vitamins A and C showed a reduction in mutagenic activity for doses of flavor that corresponds to the recommended daily − to the level of control, for dose, increased in 10 times of the recommended − in the range of 40–50%. Keywords: chromosome aberrations, food flavorings, mutagenic activity, antimutagens.